(11b-2)-5(2b+2)=-6

Simple and best practice solution for (11b-2)-5(2b+2)=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (11b-2)-5(2b+2)=-6 equation:


Simplifying
(11b + -2) + -5(2b + 2) = -6

Reorder the terms:
(-2 + 11b) + -5(2b + 2) = -6

Remove parenthesis around (-2 + 11b)
-2 + 11b + -5(2b + 2) = -6

Reorder the terms:
-2 + 11b + -5(2 + 2b) = -6
-2 + 11b + (2 * -5 + 2b * -5) = -6
-2 + 11b + (-10 + -10b) = -6

Reorder the terms:
-2 + -10 + 11b + -10b = -6

Combine like terms: -2 + -10 = -12
-12 + 11b + -10b = -6

Combine like terms: 11b + -10b = 1b
-12 + 1b = -6

Solving
-12 + 1b = -6

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 1b = -6 + 12

Combine like terms: -12 + 12 = 0
0 + 1b = -6 + 12
1b = -6 + 12

Combine like terms: -6 + 12 = 6
1b = 6

Divide each side by '1'.
b = 6

Simplifying
b = 6

See similar equations:

| -cos(x)+cos(2x)+cos(4x)=0 | | 9X=187y | | 9X=187 | | 6*3=187 | | 7x+12=2(5x-12) | | (2x+13)41=180 | | 0.4n=25 | | 12x+2x-x=9x+4 | | 2x+13-41=180 | | 9u-12=-3(u-4) | | -3(u-2)=-5u+26 | | -3v-31=2(v-3) | | 2x+13+41=180 | | -2w+5(w+4)=-1 | | -1=8(v-2)-3v | | 3y^2+12y-36x-60=0 | | 4=8(u+3)-6u | | 4(2x-1)=6x-4+2x | | -(4y-4)-(-3y-8)=4 | | 36+a=c | | 4(3x+2)=8x+6 | | -3a+16+8a=6a-9a | | 180=x+75 | | 180=x-75 | | 180=3x+27x | | x+2y+5z+10w=120 | | 10x-0.25=9x+0.375 | | G(-3)=-2w^5+8w^3-25w+4 | | G(-3)whenG(w)=-2w^5+8w^3-25w+4 | | -35=5(6f+8) | | G(w)=-2w^5+8w^3-25w+4 | | 1.1x=9.9 |

Equations solver categories